Impact of Sustainable Environmental Expenditures Policy on Air Pollution Reduction, During European Integration Framework - Ionel Bostan; Mihaela Onofrei; Elena-Doina Dascălu; Bogdan Fîrțescu; Carmen Toderașcu (Amfiteatru Economic Journal, 2016)
Pursuant to the growth of society, against the boosting of scientific and technological progress, also arises the negative effect of pollution acceleration. In this context, we relate to risks that imply the growth of pollution, especially against nuisance air pollution increase (CO, SO2, NO etc.) with major implications on the growth of greenhouse effect, the melting of the ice fields, respectively the pollution of the soil with nitrates from fertilizers intensively used in agriculture. Our study is up-to-date, as pursuant to the ONU Conference from Paris (France 2015, Conference on Climate Changes), they reached an agreement and the adopted text admits the menace of climate modifications is far more important than previously acknowledged and engages the participants to reduce their pollutant emissions. The researchers' current concerns focus on studying the effects of the redistribution of financial resources obtained by practising the `green' fiscal policy on dependent variables. Observing them, we integrate the respective variables into complex models analysed by multiple regression (both standard and robust) and the fixed effects panel on 20 European countries which also reflect the different effects on the environmental policy and the expenses it incurred. The main purpose of the analysis we aim to accomplish is the impact of the policy for environment expenditure tenable within the European framework on against nuisance air pollution attenuation. The statistical analysis aims at identifying these effects by means of regression equations (OLS), robust regression (M method), fixed and random effects, using panel data from 18 EU countries, as well as Switzerland and Turkey due to their position in relation to the community block; we will analyse the period between 1995-2013. Further to the application of multiple regression statistical methods (OLS and robust M), our results show that teimiqgdp expenses played a major role in the reduction of carbon monoxide. These are the total investments made in the mining sector; when these expenses were raised by 1% of the GDP value, there was a decrease of 11 628.3 thousand tons Cot at the level of the European countries analysed, according to the result of the OLS analysis, based on the robust M estimation.
Keywords: H23; Q58; Q53; 330; environment expenditure; European framework; air quality; environmental policy; pollution reduction; green tax